2017
DOI: 10.1589/jpts.29.1552
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the swallowing function and quality of life by oral intake level in stroke patients with dysphagia

Abstract: [Purpose] This study was conducted to compare the swallowing function and quality of life (QOL) in stroke patients with dysphagia by oral intake level. [Subjects and Methods] Seventy-nine stroke patients with dysphagia were enrolled. All subjects were evaluated by using the Swallowing Function Test (SFT) and the Swallowing Quality of Life (SWAL-QOL) questionnaire. The subjects were divided into two group based on the SFT score: oral intake (OI) and non-oral intake (NOI) groups. The SFT and SWAL-QOL scores were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 16 publications
2
19
1
6
Order By: Relevance
“…In the cases under discussion, there was no complete correspondence between swallowing functionality and the swallowing quality of life index, and this observation differed from studies on swallowing quality of life, with participants suffering from dysphagia due to non-degenerative diseases (12,13) .…”
Section: Discussioncontrasting
confidence: 64%
“…In the cases under discussion, there was no complete correspondence between swallowing functionality and the swallowing quality of life index, and this observation differed from studies on swallowing quality of life, with participants suffering from dysphagia due to non-degenerative diseases (12,13) .…”
Section: Discussioncontrasting
confidence: 64%
“…Various tools exist to guide this exploration, as evidenced by a systematic review to assess the most effective tools . Specific tools are available to assess QoL, including the swallowing QoL questionnaire, or SWAL‐QOL, for assessing QoL in stroke patients with dysphagia, validated through studies in multiple countries …”
Section: Qolmentioning
confidence: 99%
“…In assessing the impact of OI vs NOI for 79 patients diagnosed with stroke and dysphagia, a significant association was noted between swallowing function (those with OI) and QoL. This suggested that as swallowing function improves, so does QoL, as this is satisfying a basic human need on Maslow's hierarchy of needs …”
Section: Qolmentioning
confidence: 99%
See 2 more Smart Citations